Role of Phase Transfer Catalyst in Radical Polymerization of Butyl Acrylate Using Peroxomono-sulphate and Disulphate as Water Soluble Initiators – A Comparative Kinetic Study - Yogan, K.S.; Kamali, T.V.; Divya, K.; Navamani, P.; Umapathy, M.J. (Asian Journal of Chemistry, 2012)
This work describes the experimental kinetic investigation involving free radical solution polymerization of butyl acrylate initiated by water soluble peroxomono and disulphate. Polymerization was accomplished without stirring at 60 ºC in absence of oxygen in cyclohexanone/ water biphse media. The experiments were conducted at various concentrations of monomer, catalyst, initiator and various temperatures. A suitable mechanism has been propounded based on the radical polymerization.